OPTIMIZATION AND VALIDATION OF ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY COUPLED WITH TANDEM MASS SPECTROMETRY FOR QUANTIFICATION OF EFAVIRENZ IN HUMAN PLASMA - S., GAYATRI; M., SURYA; R., KARTHIK; L., VASUNDRA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study presents the optimization and validation of a sensitive, rapid, and reliable ultra-performance liquid chromatography method for the quantification of efavirenz in human plasma, using efavirenz 13C6 as the internal standard. Method: The liquid-phase extraction technique was used to isolate the internal standard and the analyte from human plasma. The extracted samples were analyzed using chromatography on an Acentis® Express 90 Å C18 column (5 cm x 4.6 mm, 2.7µm), elution carried out using a mixture of ammonium acetate buffer (5 mmol) and acetonitrile as the mobile phase (70:30). The flow rate was maintained at 0.6 ml/min with an injection volume of 5 µl. The ionization mode was negative ion electrospray, with a source energy of 150 °C. Results: The linearity of the method was confirmed by a correlation coefficient of 0.9979, and the calibration range for efavirenz was found to be 50.00-5000 ng/ml. The precision and accuracy for both intra-day and inter-day measurements showed a %CV of less than 2.3% which is within the acceptable limit. The total run time was 3 min. The mean percentage recovery was 83.9 %. Conclusion: The developed method offers a significantly reduced run time, enhancing analytical throughput and efficiency compared to previously reported methods with longer durations. This makes it particularly suitable for high-throughput analysis in routine quality control or pharmacokinetic studies.